The Penurunan Tingkat Nyeri Dismenorea dengan Pemberian Jus Wortel Pada Remaja Putri - HUSNA SARI; Erlina Hayati (Jurnal Kesehatan Komunitas, 2020)
Dysmenorrhoea is menstrual pain that forces women to rest or results in decreased performance and reduced daily activities. On average, more than 50% of women experience dysmenorrhoea in each country. One of the non-for pharmacological treatments dysmenorrhoea is using carrot juice. The purpose of this study was to decrease dysmenorrhoea pain level by giving carrot juice to young women. The research design used a quasy experiment method with one group pretest-posttest design. The sample consisted of 25 people by giving carrot juice with purposive sampling technique.Â Data collection using primary data, the instrument used was the observation sheet of the pain scale dysmenorrhoea before and after being given carrot juice. Data analysis used the Wilcoxon Signed Rank Test. The results of statistical tests with Wilcoxon before and after being given carrot juice showed that the value of Ï value was 0.001 <0.05, which means that there was a decrease of dysmenorrhoea pain level by giving carrot juice to young women , so it can be said that H0 is rejected. The conclusion is that there is a decrease of dysmenorrhoea pain level by giving carrot juice to young women. It is recommended that respondents consume carrot juice so that it can reduce the pain they feel during dysmenorrhoea.